Isolation and Characterization of Antihyperglycemic Compounds from Vigna angularis Extracts. Issue 11 (15th October 2019) - Kuriya, Kenji; Nishio, Masahiro; Ono, Nanako; Masuda, Yuichi; Katsuzaki, Hirotaka; Kondo, Shuji; Sono, Junpei; Nakamura, Masahiro; Umekawa, Hayato
Abstract : Abstract: Functional foods that inhibit α‐amylase and α‐glucosidase activity are effective for regulating the blood glucose level and preventing hyperglycemia. Extracts of adzuki beans (ABs, Vigna angularis ), widely eaten in East Asia, can inhibit α‐amylase and α‐glucosidase activity. In this study, we identified and evaluated the components in an AB water extract (ABWE) after boiling, which is an essential process for cooking ABs. The ABWE before boiling inhibited α‐amylase and α‐glucosidase activity and the boiled ABWE showed slightly stronger inhibitory effects. High‐performance liquid chromatography, liquid chromatography‐mass spectrometry, and nuclear magnetic resonance analyses identified (+)‐catechin 7‐ O ‐β‐d ‐glucopyranoside (C7G), (+)‐epicatechin 7‐ O ‐β‐d ‐glucopyranoside (E7G), and (+)‐catechin as the bioactive components in boiled ABWE. Interestingly, the quantity of E7G significantly increased after boiling (from 0% to 17.1 ± 1.3%). E7G showed stronger inhibition of α‐amylase and α‐glucosidase than C7G; the IC50 values for α‐amylase were 0.74 ± 0.04 mg/mL (C7G) and 0.40 ± 0.09 mg/mL (E7G), and for α‐glucosidase the IC50 values were 0.085 ± 0.032 mg/mL (C7G) and 0.051 ± 0.007 mg/mL (E7G). Our findings suggest that C7G and E7G are the main active components in ABWE as they inhibit α‐amylase and α‐glucosidase and their inhibitory effect is not lost after boiling. These results support the effectiveness of boiled ABs in the promotion of health. Practical Application: We identified (+)‐catechin 7‐ O ‐β‐d ‐glucopyranoside (C7G), (+)‐epicatechin 7‐ O ‐β‐d ‐glucopyranoside (E7G), and (+)‐catechin in adzuki bean extracts and commercially available boiled adzuki bean products. Interestingly, the E7G content was increased by boiling, and this compound showed strong inhibitory activity toward α‐amylase and α‐glucosidase. These results support the consumption of boiled adzuki beans to prevent acute rises in blood glucose level.